(untitled) (Journal of Pharma Insights and Research, 2024)
Rebamipide falls within the class of medications known as antiulcer agents. The process of developing and validating analytical methods is a continuous and interconnected endeavor essential to research and development, as well as quality control and assurance departments. These analytical procedures are pivotal in assessing equivalence, managing risks, and establishing product-specific acceptance criteria while ensuring result stability. Validation confirms the suitability of an analytical procedure for its intended use. Literature surveys reveal several validated analytical methods utilizing UV spectrometry, RP-HPLC, and HPTLC for the quantification of Rebamipide alone or in combination with other drugs. These methods adhere to ICH guidelines, validating parameters such as accuracy, precision, and robustness. The developed techniques are straightforward, sensitive, and reproducible, applicable for both bulk and tablet forms of Rebamipide. This comprehensive review assesses the practicality and limitations of various analytical approaches for Rebamipide analysis, offering valuable insights for researchers engaged in Rebamipide-related investigations